Benefits of Career Adaptability and Job Crafting on Career Success of Indonesian Workers during Pandemic/ Manfaat Career Adaptability dan Job Crafting pada Kesuksesan Karir Pekerja Indonesia dalam Masa Pandemi - Lakshmi, Putu Aninditha Veera; Sonata, Shella (Psikoislamika : Jurnal Psikologi dan Psikologi Islam, 2021)
Abstract: In early 2020, Indonesia entered a period of crisis due to the global pandemic caused by the Covid-19 virus. According to Indonesia Central Bureau of Statistics in 2020, many workers experienced being laid off and fired during this incident. This causes them to experience a decrease in income, changes in jobs, and hampered career success. Workers can be successful in their career in this pandemic if they are able to adapt and overcome all problems resulting from work environmental change with career adaptability, and by proactively modify and designing their work somehow along with creating a suitable work environment for his interest, skills, and competencies through job crafting. This research is a quantitative study with multiple regression analysis which aims to predict career adaptability and job crafting to career success in Indonesian workers during the pandemic. This study indicates that career adaptability and job crafting are predictors of career success for Indonesian workers during the pandemic. Career adaptability is illustrated as a person’s commitment to exploring and planning his future career, which makes him able to withstand difficult circumstances when faced with decisions and challenges in their career. Besides that, job crafting has benefits to help employees to form work-related behaviors and facilitate them to achieve success. The effective contribution given by the two predictors is 33.9%. Career adaptability and job crafting are proven have been beneficial for Indonesian workers to create their respective career successes during this pandemic period.Keywords: career adaptability; job crafting; pandemicAbstrak: Pada awal tahun 2020, Indonesia memasuki masa krisis akibat pandemi global sebagai akibat dari menyebarnya virus Covid-19. Menurut Badan Pusat Statistik tahun 2020, banyak pekerja yang mengalami PHK dan dirumahkan dalam peristiwa ini. Hal ini menyebabkan mereka mengalami penurunan pendapatan, perubahan pekerjaan, dan terhambat dalam kesuksesan karirnya. Pekerja dapat menciptakan kesuksesan karir selama pandemi jika mereka mampu beradaptasi dan mengatasi semua masalah yang diakibatkan oleh perubahan lingkungan kerja dengan career adaptability, serta secara proaktif memodifikasi dan merancang pekerjaan mereka bersamaan dengan menciptakan lingkungan kerja yang sesuai untuk minat, keterampilan dan kompetensinya melalui job crafting. Penelitian ini merupakan penelitian kuantitatif dengan analisis regresi berganda yang bertujuan untuk memprediksi career adaptability dan job crafting terhadap kesuksesan karir pekerja Indonesia pada masa pandemi. Hasil penelitian ini menunjukkan bahwa career adaptability dan job crafting merupakan prediktor keberhasilan karir tenaga kerja Indonesia pada masa pandemi. Career adaptability digambarkan sebagai komitmen seseorang untuk mengeksplorasi dan merencanakan karirnya di masa depan, yang membuatnya mampu bertahan dalam keadaan sulit ketika dihadapkan pada keputusan dan tantangan dalam karirnya. Selain itu, job crafting memiliki manfaat untuk membantu karyawan membentuk perilaku terkait pekerjaan dan memfasilitasi mereka untuk mencapai kesuksesan. Kontribusi efektif yang diberikan oleh kedua prediktor tersebut adalah 33,9%. Career adaptability dan job crafting terbukti bermanfaat bagi tenaga kerja Indonesia untuk menorehkan kesuksesan karir masing-masing selama periode pandemi ini.Kata Kunci: career adaptability; job crafting; pandemi